2010
DOI: 10.1038/leu.2010.95
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework for the identification of candidate drugs and drug targets in acute promyelocytic leukemia

Abstract: Chromosomal translocations of transcription factors generating fusion proteins with aberrant transcriptional activity are common in acute leukemia. In acute promyelocytic leukemia (APL), the promyelocytic leukemia-retinoic-acid receptor alpha (PML-RARA) fusion protein, which emerges as a consequence of the t(15;17) translocation, acts as a transcriptional repressor that blocks neutrophil differentiation at the promyelocyte (PM) stage. In this study, we used publicly available microarray data sets and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…33,[36][37][38][39] In addition, NF-kB, the key transcriptional regulator of inflammatory response, was demonstrated to be constitutively activated in various types of cancers, including AML, and to play an important role in malignant transformation in mouse models. 39,[40][41][42][43] Finally, the ability of various solid cancer cells to adapt to hypoxia and switch metabolism from oxidative phosphorylation toward glycolysis has emerged as a novel hallmark of cancer that defines more aggressive cancer phenotypes. 44 Consistent with these reports, a previous study 45 identified a cancer signature of malignant transformation that is not only shared by various types of cancers but also overlaps significantly with gene expression signatures of chronic inflammatory conditions (colitis ulcerosa, rheumatoid arthritis, systemic lupus erythematosus, Crohn's disease) and metabolic diseases (diabetes, obesity, hypercholesterolemia, atherosclerosis, cardiomyopathy).…”
Section: Discussionmentioning
confidence: 99%
“…33,[36][37][38][39] In addition, NF-kB, the key transcriptional regulator of inflammatory response, was demonstrated to be constitutively activated in various types of cancers, including AML, and to play an important role in malignant transformation in mouse models. 39,[40][41][42][43] Finally, the ability of various solid cancer cells to adapt to hypoxia and switch metabolism from oxidative phosphorylation toward glycolysis has emerged as a novel hallmark of cancer that defines more aggressive cancer phenotypes. 44 Consistent with these reports, a previous study 45 identified a cancer signature of malignant transformation that is not only shared by various types of cancers but also overlaps significantly with gene expression signatures of chronic inflammatory conditions (colitis ulcerosa, rheumatoid arthritis, systemic lupus erythematosus, Crohn's disease) and metabolic diseases (diabetes, obesity, hypercholesterolemia, atherosclerosis, cardiomyopathy).…”
Section: Discussionmentioning
confidence: 99%
“…69 Finally, a recent study reported an alternative, less biased strategy for the identification of novel drugs and drug targets in AML (Figure 4). In this study, Marstrand et al 70 identified signatures of deregulated genes in a subtype of AML, namely APL, by comparison of gene expression profiles from APL cells and their normal counterparts, that is promyelocytes, purified form healthy subjects. Subsequently, APL signatures were applied to a series of computational analyses including an in silico screen of the Connectivity MAP drug signature database.…”
Section: Gep As a Tool For Identification Of Drugs With Therapeutic Pmentioning
confidence: 99%
“…71 These analyses led to the finding that APL cells exhibit stem cell properties in terms of gene expression and transcriptional regulation, and importantly identified novel candidate drugs and targets for therapeutic interventions. 70 Significantly, the identified candidate drugs including a histone deacetylase inhibitor (trichostatin A), an inhibitor of phosphoinositide 3-kinase (PI3K) (LY294002), and an inhibitor of phospholipase A2 (PLA2) (quinacrine), were all shown to inhibit proliferation and induce apoptosis of a human APL cell line (NB4).…”
Section: Gep As a Tool For Identification Of Drugs With Therapeutic Pmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] To correct for batch effect the datasets were sorted by platform and laboratory, before RMA normalization and subsequent processing with ComBat. 10 As several platforms are represented in the dataset, only the overlapping probe sets were retained for further processing.…”
mentioning
confidence: 99%